2021
DOI: 10.1016/j.imu.2021.100670
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico analysis reveals lower transcription efficiency of C241T variant of SARS-CoV-2 with host replication factors MADP1 and hnRNP-1

Abstract: Novel severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) has claimed more than 3.3 million lives worldwide and still counting. As per the GISAID database, the genomics of SARS-CoV-2 has been extensively studied, with more than 500 genome submissions per day. Out of several hotspot mutations within the SARS-CoV-2 genome, recent research has focused mainly on the missense variants. Moreover, significantly less attention has been accorded to delineate the role of the untranslated regions (UTRs) of the S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…The 5′ UTRs interact with host factors and such interaction plays important roles in the replication, disease evolution, and aetiology [ 101 , 102 , 103 ]. In particular, during the intermittent replication process of Sars-CoV-1 genome, SL1 (RNA stem-loop 1), and SL2 support viral replication and transcription by interacting with the host MADP1 aided by nsp1 protein [ 103 , 104 ].…”
Section: Roles Of Host Znf Proteins In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The 5′ UTRs interact with host factors and such interaction plays important roles in the replication, disease evolution, and aetiology [ 101 , 102 , 103 ]. In particular, during the intermittent replication process of Sars-CoV-1 genome, SL1 (RNA stem-loop 1), and SL2 support viral replication and transcription by interacting with the host MADP1 aided by nsp1 protein [ 103 , 104 ].…”
Section: Roles Of Host Znf Proteins In Covid-19mentioning
confidence: 99%
“…MADP1 encompasses two conserved RNA-binding domains, the RNA recognition motif 1 and a Cys 2 HisCys ZNF [ 104 ] and has a critical role in determining the replication efficiency within host cells [ 103 ].…”
Section: Roles Of Host Znf Proteins In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Several other mutations like D614G in modulating higher spike infectivity and density, E484K for decreased antibody neutralization, N501Y and K417N for altering spike interacting with ACE receptor and antibodies derived from humans were reported [13,17,42]. There are several mutations which favors the host for example C241T, where viral replication efficiency with respect to host replication factors in decreased [8]. Recent reports suggest that NTD (N-Terminal Domain) is known to be supersite for antibody-mediated binding [10,25,33].…”
Section: Introductionmentioning
confidence: 99%
“…C241T was identified as a SNP or iSNV in multiple family/community transmissions and multiple non-clustered cases. According to statistics of the China National Center for Bioinformation-National Genomics Data Center (CNCB-NGDC), C241T rapidly replaced the corresponding wild-type allele in the virus population and became a feature SNP of Clade G since February 2020, and some studies have shown that C241 may confer an advantage to SARS-CoV-2 transmission ( Chaudhari et al 2021 ; Luo et al 2021 ). Considering that C241T was relatively prevalent in the Anyang virus genomes and it could not be ruled out that it arose spontaneously, we excluded it from the family/community-specific variants.…”
Section: Resultsmentioning
confidence: 99%